The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1086/425102
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Knowledge, Search Locations, and Consumer Choice

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(80 citation statements)
references
References 31 publications
3
70
0
Order By: Relevance
“…These findings provide additional support for the notion that how consumers search and where they search (e.g., Moorman et al 2004) influences choice. Further, we also contribute to the literature on search outcomes by showing that search experience (experienced cognitive effort and affect) is not just passively influenced by the decision task, but it is the result of a dynamic process that involves processing strategy selection.…”
Section: Theoretical Contributionssupporting
confidence: 64%
See 1 more Smart Citation
“…These findings provide additional support for the notion that how consumers search and where they search (e.g., Moorman et al 2004) influences choice. Further, we also contribute to the literature on search outcomes by showing that search experience (experienced cognitive effort and affect) is not just passively influenced by the decision task, but it is the result of a dynamic process that involves processing strategy selection.…”
Section: Theoretical Contributionssupporting
confidence: 64%
“…In contrast, when attributes are negatively correlated, selective processing of alternatives tends to result in examining more alternatives with better values on the prominent attribute. Given that consumer choice is affected by where consumers search for information and what information is processed (Moorman et al 2004), consumers are more likely to choose alternatives with better values on the prominent attribute.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…It should be noted as well that a dissonance may exist between objective and subjective knowledge. The previous research has reported on the various degrees of correlation between these two types of knowledge, including no significant correlation (Ellen, 1994), low correlation (.05), and high correlation (.65) (see Moorman et al, 2004), and thus, we examine the degree of correlation between the two types of knowledge for this study's participants. If a certain degree of discrepancy exists between the two types of knowledge, and their effects are opposite as hypothesized, we can speculate a three-way interaction effect, namely, that the effect of reference information will be greatest with the condition of low objective knowledge and high subjective knowledge.…”
Section: Moderating Effects Of Knowledge and Risk Propensitymentioning
confidence: 95%
“…Previous studies distinguish two types of knowledge, i.e., objective knowledge and subjective knowledge, as well as their effects on choice and information search behaviors (for a review, see Alba and Hutchinson, 2000;Moorman et al, 2004). Objective knowledge here refers to "accurate stored information," while subjective knowledge is a subjective "belief about that state of knowledge" (Moorman et al, 2004).…”
Section: Moderating Effects Of Knowledge and Risk Propensitymentioning
confidence: 99%
“…Extending previous research (Ares & Gámbaro, 2007;O'Connor, Cowan, Williams, O'Connell, & Boland, 2006), we investigate whether the identification of these segments can be improved by taking non-food-related behaviors into account, more specifically, by incorporating consumers' membership of societal organizations directly into the segmentation model. After all, food choices are not made in isolation, but are likely to fit in a broader set of general values and life choices through which consumers create and maintain a consistent selfimage (Brunsø, Scholderer, & Grunert, 2004;Moorman, Diehl, Brinberg, & Kidwell, 2004). Consumers who are concerned about, for example, animal welfare, are likely to both donate to organizations that advocate animal welfare and take this motive into account when making food choices.…”
Section: Introductionmentioning
confidence: 99%